Competitiveness Strategies for Traditional Markets: A Sharia Economic Perspective in the Digital Era and Global Market - Afril, Afril; Fahlefi, Rizal (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study analyzes the competitiveness of traditional markets amidst the pressures of modern and digital markets. Using a case study of Batusangkar Market in Tanah Datar Regency, West Sumatra, the research examines technological adaptation, merchant strategies, and the implementation of Islamic economic values. The study employs a qualitative phenomenological approach, utilizing primary data collected via semi-structured interviews with merchants possessing over 30 years of trading experience. Data analysis followed Miles and Huberman’s interactive model encompassing reduction, display, and verification validated through theoretical triangulation and member checking. The findings reveal that Batusangkar traditional market faces a decline in trade activity driven by infrastructural deficiencies, shifting consumer behaviors, and low digital literacy among merchants. Nevertheless, Sharia economic values, specifically honesty (ṣidq), justice (‘adl), trustworthiness (amānah), and mutual assistance (ta‘āwun), persist as moral anchors ensuring business continuity. These values represent a unique form of non-material competitiveness absent in modern market systems. Consequently, from an Islamic economic perspective, traditional market revitalization requires a dual focus: structural strengthening (improving infrastructure, institutions, and digital literacy) and spiritual strengthening (reinforcing trade ethics and the principle of barakah) to establish a fair, inclusive, and sustainable market aligned with maqāṣid al-syarī‘ah.